2010
DOI: 10.1371/journal.pcbi.1000846
|View full text |Cite
|
Sign up to set email alerts
|

Avalanches in a Stochastic Model of Spiking Neurons

Abstract: Neuronal avalanches are a form of spontaneous activity widely observed in cortical slices and other types of nervous tissue, both in vivo and in vitro. They are characterized by irregular, isolated population bursts when many neurons fire together, where the number of spikes per burst obeys a power law distribution. We simulate, using the Gillespie algorithm, a model of neuronal avalanches based on stochastic single neurons. The network consists of excitatory and inhibitory neurons, first with all-to-all conne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
293
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(307 citation statements)
references
References 40 publications
8
293
6
Order By: Relevance
“…(59,60). We adopt this well-established model and, for simplicity, keep only the leading terms in a power-series expansion, and rename the constants, yielding the deterministic part of Eq.…”
Section: Methodsmentioning
confidence: 99%
“…(59,60). We adopt this well-established model and, for simplicity, keep only the leading terms in a power-series expansion, and rename the constants, yielding the deterministic part of Eq.…”
Section: Methodsmentioning
confidence: 99%
“…Newman and colleagues showed that random walks generate several statistics scaling as power-laws [3], Yule introduced a process with broad applications, particularly in evolution, naturally associated to power-law distributions, and Takayasu and collaborators [12][13][14] showed that systems with aggregation and injection naturally generate clusters of size scaling as a power-law with exponent −3/2. In neuroscience, Benayoun, Wallace and Cowan have shown that neuronal networks models in a regime of balance of excitation and inhibition also provide power-law scalings of avalanches [15]. All these mechanisms are independent of any phase transition and arise away from criticality from a particular way of considering a random process.…”
Section: Introductionmentioning
confidence: 99%
“…All synapses are therefore excitatory for b > 0, and inhibitory for b < 0. The kind of collective behavior discussed here, either along the critical manifold of at its tricritical endpoint, is therefore different in nature from the chaotic dynamical features which have been emphasized in balanced networks [50][51][52], where excitatory and inhibitory effects balance each other on average.…”
Section: B Neuronal Dynamicsmentioning
confidence: 66%